ACADEMIC PUBLICATIONS: SEARCHING FOR PUBLICATIONS, TARGET READERSHIP, AND COMPARATIVE ANALYSIS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides an in-depth exploration of academic publications, focusing on the processes of searching for academic texts,understanding their target readership, and analyzing the similarities and differences between various types of academic works. It highlights key resources for finding scholarly literature, such as academic databases (Google Scholar, JSTOR, PubMed, etc.), university libraries, and open-access platforms